2018
DOI: 10.17581/bp.2018.07206
|View full text |Cite
|
Sign up to set email alerts
|

Mosses of the southern Russian Far East, an annotated check-list

Abstract: The checklist of mosses of the southern part of the Russian Far East includes 816 species and 10 infraspecific taxa with references on their distribution in seven floristic regions within Primorsky and Khabarovsky Territories, Amurskaya and Sakhlinskaya Provinces and Evreiskaya Autonomous District. Seventy one species are excluded in the course of the checklist compilation, and 59 are commented as doubtful and erroneously reported from some of the Far Eastern regions, while 8 of them doubtful for the southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
(283 reference statements)
0
23
0
6
Order By: Relevance
“…However, it is considered as widespread species in China (Hu & Wang, 2008;Zhu et al, 2010), and its finding in the Russian Far East is possible. Presence of most species was confirmed by numerous subsequent collections, except E. diversinervis, which was referred to doubtful by Cherdantseva et al (2018).…”
Section: Introductionmentioning
confidence: 87%
“…However, it is considered as widespread species in China (Hu & Wang, 2008;Zhu et al, 2010), and its finding in the Russian Far East is possible. Presence of most species was confirmed by numerous subsequent collections, except E. diversinervis, which was referred to doubtful by Cherdantseva et al (2018).…”
Section: Introductionmentioning
confidence: 87%
“…The species was described by Lazarenko (1941) and then accepted by Ignatov & Cherdantseva (1995) and Ignatov et al (2006). Cherdantseva et al (2018) suggested that this species is not distinct from F. producta, but with only brief comments, which will be complemented here.…”
Section: Introductionmentioning
confidence: 92%
“…The nomenclature follows Cherdantseva et al (2018). Abramova et al (1987) as Forsstroemia trichomitria based a single specimen from Zeysky Nature Reserve and Amur Province: "Teplyi klyuch, dwarf shrubgrass spruce forest with birch.…”
Section: I S T O F S P E C I E Smentioning
confidence: 99%